RETRACTED: Effects of Aidi injection on life quality and incidence of adverse reactions in patients with non-small cell lung cancer compared with traditional chemotherapy: a systematic review and meta-analysis - Fang, Qing; Yu, Biyun; Xu, Hui; Xu, Yuanyuan (Frontiers in Oncology, 2023)
Objective Although the clinical application value of Aidi injection when treating non-small cell lung cancer (NSCLC) patients is explained only by the effectiveness of a certain literature or the improvement of a certain evaluation index, and the result is not convincing. To evaluate the effect of Aidi injection on life quality and incidence of adverse reactions in patients with NSCLCcompared with traditional chemotherapy. Methods PubMed, EMBASE, ScienceDirect, Cochrane Library, China Journal full-text Database (CNKI), VIP full-text Database, Wanfang Database and Chinese Biomedical Literature data (CBM), search relevant Chinese and foreign periodicals, conference papers, degree papers, etc. were searched Database and China Biomedical Literature Database (CBM) to search case-control trials of Aidi injection when treating NSCLC patients. The retrieval period begins with the establishment of the database and ends when the database is closed. Cochrane Handbook 5.3 was adopted to assess the bias risk of each contained literature based on independently extracted data by two researchers. A meta-analysis of the collected data was carried out using RevMan5.3 statistical software. Results 2306 articles were retrieved by computer database, 1422 articles were harvested by excluding repeated studies, 865 articles were harvested by preliminary reading of article titles and abstracts, and 533 articles were initially contained by excluding unrelated studies, reviews, case reports and uncontrolled articles, and then the full text of the literature was carefully read. Eight clinical controlled studies were finally included, with a total of 784 samples, after excluding 525 literatures with incomplete data and no primary outcome indicators. Data from the contained studies were not noticeably heterogeneous in the meta-analysis of treatment effectiveness. The fixed effect model analysis indicated that the treatment effective rate of the study group was noticeably better, and the difference was statistically significant(P<0.05). The findings of the heterogeneity test were clearly heterogeneous among the contained research data, according to the meta-analysis of the levels of T lymphocyte subsets following treatment. The random effect model analysis indicated that the improvement of the cellular immune function of the research group was obvious, and the difference was statistically significant (P<0.05). According to the meta-analysis of the life quality scores after treatment, data from the contained research were evidently heterogeneous, according to results of the heterogeneity test. The random effect model analysis indicated that the life quality of the study group was noticeably higher, and the difference was statistically significant (P<0.05). The levels of serum vascular endothelial growth factor (VEGF) after treatment were measured by meta. Data from the contained research were evidently heterogeneous, according to results of the heterogeneity test. Random effect model analysis indicated that the level of serum VEGF in the study group was noticeably lower, and the difference was not statistically significant (P>0.05). A meta-analysis was conducted on the incidence of adverse reactions after treatment. The results of the heterogeneity test indicated that data from the contained research were evidently heterogeneous. The incidence was noticeably lower, and the difference was statistically significant (P<0.05). The funnel chart was drawn based on the effective rate of treatment, the level of T lymphocyte subsets, the score of life quality, the level of serum VEGF and the incidence of adverse reactions, and the publication bias analysis was carried out. The results indicated that most of the funnel maps were symmetrical and a small part of them were asymmetrical, suggesting that despite the heterogeneity of the study and the small number of included literatures, a publication bias was apparent in the included literature. Conclusion Based on routine chemotherapy associated with Aidi injection, the therapeutic effect of NSCLC patients can be noticeably enhanced, the effective rate of treatment can be noticeably promoted, the immune function and life quality can be improved, and the incidence of adverse reactions is low, which is worth popularizing in clinical practice, but several studies and follow-ups are needed to improve methodological quality and to verify the results over a longer period of time.